GOVERNANCE AND INSTITUTIONAL PERFORMANCE OF THE AUTONOMOUS REGION IN MUSLIM MINDANAO (ARMM), PHILIPPINES: A CRITICAL ASSESSMENT OF ITS PUBLIC SERVICE DELIVERY FROM THE YEAR 1991 TO 2015. - Milhaya Langco (Yayasan Wayan Marwan Pulungan, 2025)
This aims to evaluate the Autonomous Region in Muslim Mindanao's (ARMM) performance in fulfilling its mandated functions, specifically in addressing the difficulties and problems that the region faced from 1991 to 2015, including poverty, political instability, a lack of peace and order, and inadequate provision of basic social services. Utilizing secondary data and a qualitative research methodology, the study assessed the ARMM's performance and responses to regional challenges. Additionally, it seeks to examine the actions of the ARMM since it was given the authority to rule the Muslim community in the Southern part of the Philippines. The findings suggest that hunger and poverty remain significant issues in the region. The former ARMM has consistently ranked lowest in terms of the availability of fundamental social services, although other parts of the Philippines continue to experience economic growth. The ARMM government's successful programs and interventions did not address the most critical issue facing the community: access to high-quality education. These findings suggest that even in fundamental areas, such as the rigorous execution of programs aimed at reducing poverty and the delivery of social services like access to clean water, sanitary facilities, and medical care, the ARMM as a whole was unable to fulfill its mandated duties. Additionally, a significant issue is the community's widespread culture of silence, even though crime remains prevalent in the area.